Theoretical View on The Position of The Consumer in Acceptance of Product Advertising - Ida Bagus Gede Agustya Mahaputra; I Made Aditya Mantara Putra (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2022)
Commercial players have greater and more comprehensive resources, marketing and relationships than consumers. It can even be said that consumers have relatively limited legal awareness and their rights as consumers, so that perpetrators are often treated unfairly against companies. The injustice in question can be observed in one of the advertisements. Entrepreneurs are not clear in the legislation on consumer protection, the structure of legal responsibility for advertising that harms consumers. This study aims to examine the philosophical nature of consumer legal protection in relation to harmful advertising. The method used in this study is a type of legal normative research method. Based on the results of the study, this study indicated that consumer protection arrangements in Indonesia are still not optimal considering that contracts do not cover the legal responsibilities of economic actors who broadcast products advertised by advertising companies. Of course, the philosophical aspects involved in looking at the Pancasila perspective are Precepts 2 and 5 which contain elements of human rights. The principle of fairness regarding the rights and obligations of entrepreneurs is therefore not balanced. More appropriate action is needed to strictly control the advertisements on broadcasters. This can become legal knowledge for consumers, law enforcement officers, businesses or broadcasters to pay attention to the advertisements that are broadcast so as not to cause consumers to lose right.